Service quality perception and patient satisfaction: evidence from private hospitals in Kathmandu (The International Research Journal of Management Science, 2017)
Main purpose of this paper is to examine the level of service quality of Private hospitals with dependent (Patient Satisfaction) and independent variables such as responsiveness, reliability, assurance, empathy and tangibility. Self-administered structured questionnaire among 100 respondents of Kathmandu, Lalitpur and Patan is executed by convenience as well as judgment sampling. Coefficient, regression, correlation analysis and ANOVA are the basis for statistical analysis. In order to test the stated hypotheses, descriptive design has been applied. It has been revealed that private hospitals should focus more on convenient OPD and ward location. In addition, doctors should maintain the confidentiality of the patients. As a result, all the dimensions of service quality i.e. responsiveness, reliability, assurance, empathy and tangibility are positively correlated with respondent’s satisfaction. However, tangibility and assurance are strongly correlated in perceived service quality satisfaction offered by private hospitals.